CFD analysis of particle shape and Reynolds number on heat transfer characteristics of nanofluid in heated tube - KURT, MUSTAFA; EVRAN, SAVAŞ (My University, 2024)
Various nanoparticles have been used to increase the heat transfer characteristics (HTC) of nanofluids in the heated tube. The use of various shapes of the same nanoparticle can have major impact on the HTC. In this study, computational fluid dynamics (CFD) analysis of the impact of particle shape (Brick and Platelet) and Reynolds (Re) number (4,500, 6,000, 7,500, and 9,000) on the HTC of nanofluid in the heated tube was carried out in accordance with Taguchi method. Heat transfer coefficient, Nusselt (Nu) number, performance evaluation criteria, and average static pressure drop were chosen as HTC. CFD analyses for 1% Fe3O4 nanofluids in ANSYS Fluent software were performed in accordance with L8 orthogonal array. Particle shape and Re number were selected as the first and second factors, respectively. Signal/noise analysis was used to decide optimumlevels and impact direction on HTC for each factor, whereas analysis of variance was implemented to define the importance levels and percentage impact ratios of the factors. According to the results obtained from the study, the nanofluids with platelet nanoparticles have a higher impact on the heat transfer coefficient compared to Brick nanoparticles. Although the increase in the Re number causes an increase in the heat transfer coefficient, Nu number, and average static pressure drop, it does not have any effect on the performance evaluation criteria. The results obtained from this study can be used as a guidance for experimental studies. Keywords: ANOVA, CFD, heat transfer, nanofluids, Taguchi method
Keywords: Makina Mühendisliği; Enerji; Makina Teorisi ve Dinamiği; Mekanik; Sonlu Elemanlar Yöntemi; Havacılık ve Uzay Mühendisliği; Uzay Mühendisliği; Görev; Matematiksel Modelleme teknikleri; Mühendislik ve Teknoloji; Mechanical Engineering; Energy; Machine Theory and Dynamics; Mechanical; Finite Element Methods; Aeronautical and Space Engineering; Space Engineering; Task; Mathematical Modeling Techniques; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; MÜHENDİSLİK, MEKANİK; ENERJİ VE YAKITLAR; ASTRONOMİ VE ASTROFİZİK; MÜHENDİSLİK, HAVACILIK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ENGINEERING, MECHANICAL; ENERGY & FUELS; ASTRONOMY & ASTROPHYSICS; ENGINEERING, AEROSPACE; Astronomi ve Astrofizik; Fizik ve Astronomi (çeşitli); Genel Fizik ve Astronomi; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; Astronomy and Astrophysics; Physics and Astronomy (miscellaneous); General Physics and Astronomy; Computational Mechanics; Automotive Engineering; Aerospace Engineering; Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences; ANOVA; CFD; heat transfer; nanofluids; Taguchi method